PERJANJIAN PERKAWINAN ANTARA SUAMI ISTRI BERDASARKAN UNDANG-UNDANG PERKAWINAN - Marsidah, Marsidah (Solusi, 2020)
Marriage agreements between husband and wife can be done before the marriage is carried out. Many marriage agreements are carried out in relation to assets included in shared assets. Marriage agreements in Indonesia are not very popular, therefore, many husbands and wives do not carry out these marriage agreements. This is because many do not know that Law Number 16 Year 2019 regulates marriage agreements. The problem in this paper is how the legal strength of a marriage agreement according to Law Number 1 of 1974 as amended by Law Number 16 of 2019 concerning Marriage. This type of research used in this study is a type of normative written legal research that examines the legal strength of marriage agreements according to Law Number 16 of 2019. Data collection techniques used are secondary data by taking data obtained from books and legislation called literature review. Then it can be concluded that the marriage agreement arrangement is contained in Law Number 16 of 2019 and compilation of Islamic law. If husband and wife do not obey the marriage agreement that has been contained in the Marriage Certificate, then the marriage can be requested for cancellation and can be used as a basis for filing for divorce in the Religious Court.